MITOS DATU AYUH DALAM RELIGI ARUH; AJARAN LISAN TENTANG PERSAUDARAAN BANJAR MUSLIM DENGAN ORANG DAYAK LOKSAD - Moh Soehadha (Ri'ayah: Jurnal Sosial dan Keagamaan, 2019)
Aruh religion is a system of ideas for Loksado people to work on the environment and give meaning to all activities in daily life. Religious knowledge is transformed from generation to generation through oral traditions which are considered sacred literature. A number of myths found in Aruh religious teachings underlie various religious actions such as in rice harvest rituals, rites of passage, healing rituals (babalian) and also social, economic and political actions in their daily lives. The development of a system of oral teachings among local people such as the Loksado people can be associated with the concept of symbolism in anthropology. Humans are symbolic creatures (animal symbolicum), that symbolic thinking and symbolic behavior are human characteristics . Various hopes, dreams, and thoughts that are sometimes difficult to accept by the human mind itself, manifested in various actions and symbolic works. Among the forms of symbolization carried out by humans are myths. As a symbolic expression, myths can almost be found in various cultural symptoms in all societies.